Lanzamiento de la marca BonVid: una nueva marca de limpieza en el Perú - Mendoza Vargas, Denisse Eleana (2022)
As a result of the COVID-19 pandemic, the home cleaning industry has become very relevant due to the fear of initial contagion among the population. This was becoming a new habit among Peruvians to the point that awareness about the importance of keeping our belongings clean and cared for, more specifically speaking, our clothes, will continue. For this reason, the BonVid brand was created, which offers the market a new format of detergent called Power Pods that claim to have the same efficiency as the traditional format but with less investment time when used by the consumer as it is a more comfortable presentation. And simple. The purpose of the brand is "To be the most comfortable and practical option for cleaning clothes, to be able to continue working with style while taking care of oneself." The aim is to motivate the consumer to prioritize their personal care and at the same time leave their clothing in good condition, using an eco-friendly product that contributes to caring for the environment with its packaging. BonVid continued a 3-month launch campaign to build awareness and brand awareness among its customers.